When Your Friend is My Friend: How Loyalty Prompts Support for Indirect Ties in Moral Dilemmas - Berry, Zachariah; Hildreth, John Angus D. (Organization Science, 2025)
How are some criminals able to get away with wrongdoing for months or even years? Here, we consider the role of loyalty in facilitating networks of support for wrongdoers, examining whether the obligations of loyalty to direct ties (here, brokers) transfer through individuals’ social networks to their indirect ties, prompting them to support those indirect ties in moral dilemmas. Integrating research on brokering, loyalty, relational identity, and social norms, we propose that loyalty to a broker will prompt an individual to support an indirect tie accused of wrongdoing because loyalty activates one’s relational identity with the broker, which highlights the descriptive and relational injunctive norms associated with their role, leading them to view the broker’s request to support an indirect tie accused of wrongdoing as falling within the bounds of their loyalty-based obligations to the broker. Specifically, these norms reveal to the actor their benevolence-based trust in the broker, their value alignment with the broker, and relational concerns for not granting the broker’s request. We further demonstrate how a broker’s history of creating divisions between people moderates how the actor sees the broker and reduces their willingness to grant the request. Across 11 preregistered studies (n = 2,249)—10 experiments and a field study—we found support for our hypotheses: the obligations of loyalty to brokers did indeed transfer to indirect ties accused of wrongdoing, regardless of the type of wrongdoing or strength of evidence presented against the accused. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2023.18003 .